Activity, acoustic repertoire and social interactions of the red toadlet, Brachycephalus pitanga (Anura: Brachycephalidae) - de Oliveira, Eliziane Garcia [UNESP]; Haddad, Célio Fernando Baptista [UNESP] (My University, 2017)
The genus Brachycephalus is endemic to the Brazilian Atlantic Forest with most of its known species having been described only recently. In contrast to growing body of knowledge regarding the taxonomy of this genus, there remains a lack of general knowledge about their biology. Herein, we aim to describe the acoustic repertoire, social interactions between males and temporal pattern of reproductive activity of Brachycephalus pitanga. Humidity was the main explanatory factor for variation in the number of calling males throughout the year. We describe five calls types for the species: advertisement, territorial, encounter, warm-up and antiphony. The contexts in which these call types are emitted and their temporal and spectral parameters are discussed. During territorial disputes male frogs exhibited increasing levels of aggressiveness, beginning with the emission of territorial calls, escalating through encounter calls and visual signals and culminating in physical contests.
Keywords: Atlantic forest; Behavior; Visual communication; Vocalizations